A prospective observational study of pharmacological attitude in psychiatric population - Gagan Shant Parkash; Harminder Singh; Rahul Deb; Medi Nagapadma (Telangana Journal of Psychiatry)
Objectives: The study was done (1) to evaluate the attitude of patients toward medications related to psychiatric illnesses and (2) to determine the association of attitude with adherence. Methods: A prospective observational study was carried out at the Department of Psychiatry of a tertiary care hospital in Punjab. A total of 425 patients admitted at the indoor and outdoor departments, from July 2022 to June 2023, were included. Morisky-8 scale and Drug Attitude Inventory-10 scale were used for the assessment of patients. Results: Among 425 patients, 173 (40.7%) patients were nonadherent, out of which 377 (88.7%) patients had pharmacophilic attitude and 48 (11.3%) had pharmacophobic attitude. Compared to pharmacophilic attitude group, pharmacophobic attitude group had significantly more rural distribution (83.3% vs. 66.31%, P = 0.017), more illiterate (16.67% vs. 5.04%, P = 0.002), and less unemployed (27.08% vs. 44.03%, P = 0.025). Patients with schizophrenia were significantly more in pharmacophobic group than pharmacophilic group (10.42% vs. 3.71%, P = 0.034). Anxiety disorder, bipolar disorder, and depression showed no association with attitude. Among 173 nonadherent patients, 127 were pharmacophilic and 46 were pharmacophobic, whereas among 252 adherent patients, only 2 were pharmacophobic. Pharmacophobic attitude showed a significant association with nonadherence to the medications (P < 0.0001). Conclusion: It can be concluded that 11.3% of patients had pharmacophobic attitude, and pharmacophobic attitude is significantly associated with non-adherence to the medications. Among the psychiatric disorders schizophrenia, patients had significantly higher pharmacophobic attitude.